PENGGUNAAN DAKWAAN KUMULATIF SUBSIDAIR DALAM PEMBUKTIAN PERKARA PEMBUNUHAN BERENCANA DALAM PUTUSAN NOMOR: 1466/PID.B/2023/PN PLG - Rendi Yurisdika Ardy; Muhammad Rustamaji (Sebelas Maret University, 2026)
This research aims to examine the conformity of the application of the cumulative-subsidiary indictment in a premeditated murder case with the provisions of the Indonesian Code of Criminal Procedure (KUHAP) and the judges' considerations in rendering the sentencing decision in Verdict Number: 1466/Pid.B/2023/PN Plg. This study adopts a normative legal research type with a prescriptive and applied nature. The approach employed is a case-based approach, which involves analyzing cases related to legal issues that have reached a final and binding decision. Legal materials were collected through library research. The legal materials used in this study include primary and secondary legal materials. The analysis technique applied to the legal materials is deductive syllogism. The findings of this research indicate that the application of the cumulative-subsidiary indictment in the Palembang District Court Verdict Number: 1466/Pid.B/2023/PN Plg is in accordance with the provisions of the KUHAP. The judges' considerations in deciding the case align with the elements of Article 340 of the Indonesian Penal Code (KUHP) in conjunction with Article 55 Paragraph (1) Subparagraph 1 of the KUHP, complemented by the elements of Article 353 Paragraph (2) of the KUHP in conjunction with Article 55 Paragraph (1) Subparagraph 1 of the KUHP. These elements served as the basis for the judges' decision to impose the death penalty. Furthermore, the panel of judges rendered their decision on the defendant based on both juridical and non-juridical considerations, as well as the provisions of Article 183 of the Code of Criminal Procedure.